Pengaruh Durasi Pemakaian Gawai Dengan Risiko Keterlambatan Bicara Pada Anak Usia 2-5 Tahun - Chandrawangsa, Florenza Athena (Politeknik Kementerian Kesehatan Banjarmasin, 2025)
This study aimed to evaluate the relationship between gadget use duration and the risk of speech delay in children aged 2-5 years at Puskesmas Grogol, Jakarta, from December 2024 to February 2025. A cross-sectional study involved 45 children selected through total sampling. Data were collected using a questionnaire for gadget use duration and the Pre-Developmental Screening Questionnaire (KPSP) to assess speech delay risk, analyzed with the Spearman correlation test. Results showed a significant association between gadget use duration and speech delay risk (p = 0.035, p < 0.05), with 48.9% of children using gadgets for more than 2 hours daily at risk of speech delay. Excessive gadget use may hinder children’s language development. This study recommends parental supervision in regulating gadget use time and enhancing verbal stimulation to support children’s speech development.